SETTING GOALS ACCORDING TO STUDENTS’ TRUE LANGUAGE NEEDS - Norbekova, Gulruh (Журнал иностранных языков и лингвистики, 2021)
Teaching a foreign language process has become not only more intensive, but also significantly more successful. One of them is the tendency to strengthen the communicative orientation of the educational process. This trend was not born today or yesterday: making the learning process closer to the communication process by its nature has been undertaken for a long time. As the scientific research of methodologists and the practical search for teachers improving, it became clear that we were dealing not only with a stable trend, but also with an innovative teaching method based on latest curriculum.